Assessing water security in Central Asia through a Delphi method and a clustering analysis - Assubayeva, Aliya; Xenarios, Stefanos; Li, Albina; Fazli, Siamac (Frontiers in Environmental Science, 2022)
The accessibility to freshwater sources and even allocation among different uses has become one of the most challenging sustainability aspects, especially in developing and transition economies, where a rapid increase in water consumption and poor management practices are more frequent. Water security has been adopted as a relatively new concept to encompass the relevant dimensions for the sustainable management of freshwater resources. Still, water security remains a rather abstract notion without well-established and measurable indicators. Central Asia (CA) is a region where water security was prioritized after the Soviet dissolution in 1991; however, several socio-economic, environmental, and transboundary aspects hinder establishing a common understanding. In this study, we have attempted to synopsize the concept of water security in CA as perceived by the views of water professionals with experience and expertise in the region. We applied a Delphi method and analyzed its outcome with clustering and regression analysis to better comprehend the agreement rate among water professionals on critical aspects of water security in the CA region. Our devised methodology can quantify the general agreement rate among professionals and assess the behavioural trends for iterative Delphi rounds. The findings suggest that the economic dimension of water security in CA is the ultimate priority for nearly all water professionals, while the national priorities for each CA county are not identical. The study anticipates identifying the elements needed for a commonly agreed water security framework in CA and offering methodological insights for the assessment of socio-ecological challenges.